PENERAPAN DATA MINING UNTUK REKOMENDASI PAKET PERNIKAHAN MENGGUNAKAN METODE ALGORITMA APRIORI - Nanchy Adeliana Br S. Muham; Saljuna Hayu Rangkuti; Sion Putri Zalukhu; Evta Indra; Delima Sitanggang (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
SM Wedding Decoration is a place that provides services to take care of everything related to weddings. For example, wedding decorations, wedding organizers, and wedding planners. SM Wedding Decoration has several wedding packages that can be offered to customers. The many packages available make the bride and groom or customers confused to determine which wedding package is suitable for their wedding. The a priori algorithm method is used in this study to find recommendations for wedding packages based on existing transaction data and to improve the company's strategy and sales of other wedding packages. The Apriori algorithm is used to help computers learn patterns of association rules. This algorithm looks for a set of things that match the given criteria or sequence and has a certain frequency value. From this research, customers tend to order Photographer & Documentation and MUA → Deluxe packages more often, and these orders account for 44% of all package order transaction data. Package order transaction data for MUA→Deluxe package is 41.3%. Transaction data for the Photographer & Documentation package → Deluxe Package is 41.2%. And the transaction data for ordering the MUA → Premium Deluxe Package package is 41.3%.